Tunable all-optical actively mode-locked fiber laser at 2 µm based on tellurite photonic crystal fiber. (4th May 2018) - Wu, Xu; Huang, Pan; Huang, Tianye; Wu, Zhichao; Cheng, Zhuo; Chen, Bingwei; Ren, Kaixuan; Fu, Songnian
Abstract: Although thulium-doped fiber lasers operating at 2 µ m have been intensively investigated, lasers with high repetition rate (up to several tens of gigahertz) and tunable output characteristics are difficult to achieve at this band. In this paper, an all-optical actively mode-locked fiber laser is proposed for this purpose. By employing a section of specially-designed highly nonlinear group-velocity-matched tellurite photonic crystal fiber as the mode-locker, the proposed thulium-doped fiber laser can easily produce stable pulses with tunable pulse width and repetition rate up to 40 GHz. Moreover, through investigating the pulse dynamics in the cavity, a transfer-limited soliton pulse is successfully achieved. The proposed laser can find application in future optical fiber communication systems at 2 µ m.